Genetic or Toxicant-Induced Disruption of Vesicular Monoamine Storage and Global Metabolic Profiling in Caenorhabditis elegans. (4th February 2021) - Bradner, Joshua M; Kalia, Vrinda; Lau, Fion K; Sharma, Monica; Bucher, Meghan L; Johnson, Michelle; Chen, Merry; Walker, Douglas I; Jones, Dean P; Miller, Gary W
Abstract: The proper storage and release of monoamines contributes to a wide range of neuronal activity. Here, we examine the effects of altered vesicular monoamine transport in the nematode Caenorhabditis elegans . The gene cat-1 is responsible for the encoding of the vesicular monoamine transporter (VMAT) in C. elegans and is analogous to the mammalian vesicular monoamine transporter 2 (VMAT2). Our laboratory has previously shown that reduced VMAT2 activity confers vulnerability on catecholamine neurons in mice. The purpose of this article was to determine whether this function is conserved and to determine the impact of reduced VMAT activity in C. elegans . Here we show that deletion of cat-1 /VMAT increases sensitivity to the neurotoxicant 1-methyl-4-phenylpyridinium (MPP + ) as measured by enhanced degeneration of dopamine neurons. Reduced cat-1 /VMAT also induces changes in dopamine-mediated behaviors. High-resolution mass spectrometry-based metabolomics in the whole organism reveals changes in amino acid metabolism, including tyrosine metabolism in the cat-1 /VMAT mutants. Treatment with MPP + disrupted tryptophan metabolism. Both conditions altered glycerophospholipid metabolism, suggesting a convergent pathway of neuronal dysfunction. Our results demonstrate the evolutionarily conserved nature of monoamine function in C. elegans and further suggest that high-resolution mass spectrometry-based metabolomics can be used in this model to study environmental and genetic contributors to complex human disease.